MENINGKATKAN PEMAHAMAN DAN PARTISIPASI UMAT DALAM MENGIKUTI ADORASI DI WILAYAH WALIKOTA B PAROKI SANTA MARIA ASSUMPTA KEUSKUPAN AGUNG KUPANG - Wea, Melania; Ngongo, Maria Hendrita Lidya; Abatan, Yovince (Pastoralia Jurnal Penelitian Dosen, 2020)
Adoration is the most harmonious way of expressing the relationship between the celebration of the commemoration of the Lord's sacrifice and His continued presence in the Sacrament of the Altar. The basic reason why the author raised this title as research is because in the area of Mayor B of the Parish of Santa Maria Assumpta, the people who take part in Adoration are very inversely proportional to mass on Sundays or on major holidays and there are people who follow Adoration because they have personal problems. Therefore, this study aims to determine the extent of understanding of the people in the area of Mayor B of the Santa Maria Assumpta parish in participating in Adoration. The method used in this research is a qualitative method, the reason the author uses this method is because this method is considered the most appropriate to the problem that the writer chose. This method aims to process natural data found in the field without engineering, and displays in the form of a systematic and real situation description in the form of a collection of sentences. Based on the results of the interview data analysis, the writer knows that the people in the area of Mayor B of the Parish of Santa Maria Assumpta have not realized the importance of participating in Adoration because they think that attending mass on Sundays or on major holidays is much more important by participating in Adoration. The inhibiting factors are busyness, no willingness from within (lazy) and association. The effort that needs to be done is the need for catechesis regarding the importance of participating in Adoration, as well as sharing of experiences of faith in order to encourage people to participate in Adoration.